PERAN LOCUS OF CONTROL INTERNAL DALAM MEMODERASI PENGARUH MOTIVASI KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN UNIVERSITAS MAHASARASWATI DENPASAR - Ade Agus Diama Purwa Diputra; Gusti Ayu Sugiati; Ni Wayan Sitiari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
This research was conducted at the Rectorate of Mahasaraswati University Denpasar by distributing questionnaires at the address Jl. Cambodia No.11A, Dangin Puri Kangin, Kec. North Denpasar, Denpasar City, Bali. The purpose of this research is to analyze the influence of the role of internal locus of control in moderating the influence of work motivation and organizational commitment on employee performance. The population in this study was all 55 employees within the Rectorate of Mahasaraswati University Denpasar. The data analysis technique used in this research is path analysis using the SPSS program. The results of this research show that employee work motivation has a positive and significant influence on employee performance. Employees' organizational commitment has a positive and significant influence on employee performance. The influence of work motivation on employee performance increases due to the moderating effect of internal locus of control at the Mahasaraswati University Rectorate. The influence of organizational commitment on employee performance increases due to the moderating effect of internal locus of control at the Mahasaraswati University Rectorate. This research is still very possible to be developed because work motivation, organizational commitment, internal locus of control are only able to explain employee performance by 43.5% (percent). Further researchers can use other variables such as job rotation, salary and others that might influence employee performance.